Stability of medial entorhinal cortex representations over time. Issue 3 (2nd September 2018) - Diehl, Geoffrey W.; Hon, Olivia J.; Leutgeb, Stefan; Leutgeb, Jill K.
Abstract: Distinct functional cell types in the medial entorhinal cortex (mEC) have been shown to represent different aspects of experiences. To further characterize mEC cell populations, we examined whether spatial representations of neurons in mEC superficial layers depended on the scale of the environment and changed over extended time periods. Accordingly, mEC cells were recorded while rats repeatedly foraged in a small or a large environment in sessions that were separated by time intervals from minutes to hours. Comparing between large and small environments, we found that the overall precision of grid and non‐grid cell spatial maps was higher in smaller environments. When examining the stability of spatial firing patterns over time, differences and similarities were observed across cell types. Within‐session stability was higher for grid cells than for non‐grid cell populations. Despite differences in baseline stability between cell types, stability levels remained consistent over time between sessions, up to 1 hr. Even for sessions separated by 6 hrs, activity patterns of grid cells and of most non‐grid cells lacked any systematic decrease in spatial similarity over time. However, a subset of 15% of mEC non‐grid cells recorded preferentially from layer III exhibited dramatic, time dependent changes in firing patterns across 6 hrs, reminiscent of previous characterizations of the hippocampal CA2 subregion. Collectively, our data suggest that mEC grid cell input to hippocampus in conjunction with many time invariant non‐grid cells may aid in stabilizing hippocampal spatial maps, while a subset of time varying non‐grid cells could provide complementary temporal information.